2022
DOI: 10.1039/d2py01001a
|View full text |Cite
|
Sign up to set email alerts
|

A one-component phosphonium borane Lewis pair serves as a dual initiator and catalyst in the ring-opening alternating copolymerization of anhydrides and epoxides

Abstract: Lewis pairs as synergistic catalysts have demonstrated versatile adaptabilities towards different monomers. Herein, we converted bi-component Lewis pair into one-component Lewis pair by integrating Lewis acid and ionic Lewis base...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…However, the catalytic efficiency was relatively low and the molecular weight of the reported copolymer needed further improvements. In contrast to binary organoborane based Lewis pair, we and others showed that one‐component organoborane based Lewis pair exhibited enhanced activity in the ROP 35,36,39–43 …”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…However, the catalytic efficiency was relatively low and the molecular weight of the reported copolymer needed further improvements. In contrast to binary organoborane based Lewis pair, we and others showed that one‐component organoborane based Lewis pair exhibited enhanced activity in the ROP 35,36,39–43 …”
Section: Introductionmentioning
confidence: 65%
“…Our group focused on the ring-opening polymerization (ROP) and ROAP using Lewis pair organocatalysts. 34,35 Previously, we reported phosphonium bisborane PPB-Br showed synergistic effect on the ROP of PO and exhibited good tolerance of various functional groups to prepared diverse functionalized PPOs. 36,37 We reasoned that the introduction of acetal units into the polyether backbone could effectively empower the degradability of the material and improve the scope and use of the material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group focused on the ring-opening polymerization (ROP) and ROAP using Lewis pair organocatalysts. 34,35 We first reported phosphonium bisborane PPB showed synergistic effect on the ROP of PO and exhibited good tolerance of various functional groups to prepared diverse functionalized PPOs. 36 We reasoned that the introduction of acetal units into the polyether backbone could effectively empower the degradability of the material and improve the scope and use of the material.…”
Section: Introductionmentioning
confidence: 99%